Unveiling the guardians of the genome: The dynamic role of histones in DNA organization and disease - Vijayalakshmi, Periyasamy; Gowdham, Manivel; Dinesh, Dhurvas Chandrasekaran; Sibiya, Ashokkumar; Vaseeharan, Baskaralingam; Selvaraj, Chandrabose (Advances in protein chemistry and structural biology, 2025)
Histones are positively charged proteins found in the chromatin of eukaryotic cells. They regulate gene expression and are required for the organization and packaging of DNA within the nucleus. Histones are extremely conserved, allowing for transcription, replication, and repair. This review delves into their complex structure and function in DNA assembly, their role in nucleosome assembly, and the higher-order chromatin structures they generate. We look at the five different types of histone proteins: H1, H2A, H2B, H3, H4, and their variations. These histones bind with DNA to produce nucleosomes, the basic units of chromatin that are essential for compacting DNA and controlling its accessibility. Their dynamic control of chromatin accessibility has important implications for genomic stability and cellular activities. We elucidate regulatory mechanisms in both normal and pathological situations by investigating their structural features, diverse interaction mechanisms, and chromatin impact. In addition, we discuss the functions of histone post-translational modifications (PTMs) and their significance in various disorders. These alterations, which include methylation, acetylation, phosphorylation, and ubiquitination, are crucial in regulating histone function and chromatin dynamics. We specifically describe and explore the role of changed histones in the evolution of cancer, neurological disorders, sepsis, autoimmune illnesses, and inflammatory conditions. This comprehensive review emphasizes histone's critical role in genomic integrity and their potential as therapeutic targets in various diseases.
Keywords: Post-translational modifications (PTMs); nukleozomy; DNA; Nucleosomes; posttranslační úpravy proteinů; Chromatin; Gene expression; histony; Neoplasms; Histones; Disease; Genomic stability; Protein Processing, Post-Translational; zvířata; Humans; nádory; chromatin; lidé; Animals